Perbandingan Kinerja Indeks Dow Jones, DAX, Nikkei 225, Kospi dan IHSG di Masa Pandemi Covid-19 - Murdiyanto, Edi; Akbar, Taufik (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2021)
The Covid-19 pandemic is an outbreak that has an impact not only on the health sector, but also on almost all elements of human life in many countries. the economy was hit hard, as reflected in the decline in the world stock index. This is the background for the author to conduct research on the performance of world stock indices represented by the Dow Jones Industrial Average, DAX, Nikkei 225, Kospi and JCI indeces. The research method uses descriptive statistics with frequency distribution methods. Secondary data comes from literacy studies in the form of statistical data. The results showed a decrease in all indices. The decline started in the second week of February with the deepest decline in March, by the end of the year all indexes experienced a rebound. There is still uncertainty in the future economy due to the pandemic which is still not over. Economic policies in each country are certainly different and affect market optimism. Choosing the right portfolio with careful consideration and always monitoring economic developments is certainly a common thing to do.